EFFECT OF DIFFERENT SOIL WATER AVAILABLE LEVELS ON THE GROWTH AND ON THE CO2 EXCHANGEOF YOUNG ERVA-MATE PLANTS - PINTRO, José Carlos; FLORES, Feliciano Edi Vieira (Scientia Agraria, 2003)
The influence of different levels of soil water availability on the growth, CO2 exchange, and the leaves relative water content (RWC) of young plants of erva-mate (Ilex paraguariensis St. Hil.) were studied under controlled conditions during a period of 315 days. The foreseen treatments corresponded to 3 water available levels for plants: treatment 1 (T-1): soil moisture at -0.03 MPa , treatment 2 (T-2): soil moisture at 80% of water quantity used in T-1, and treatment 3 (T-3): soil moisture at 65% of water quantity used in T-1. The height of the plants, the number of the leaves, the total leaf area, the exchange of CO2, and the RWC in the leaves were evaluated. The best results, with significant increment of the values of height, number of the leaves, and total leaf area were verified in treatment T-2 in relation to T-1 and T-3. The values of leaves CO2 exchange were not significantly different among the treatments. However, the reductions of the CO2 exchange values from 2 to 4 days after irrigation were 39% in T-1, 15% in T-2, and 35% in T-3. The RWC values reduced with time after irrigation. The reductions were 4.55 in T-1, 5.48% in T-2, and 6.85% in T-3. The best conditions of soil availability and the adaptation of photosynthetic process verified in the treatment T-2 could be justified the better growth of erva-mate plants in relation to treatments T-1 and T-3.